Entrepreneurial orientation and performance in the context of market dynamism: similarities and differences between Polish and Bulgarian companies - Wójcik-Karpacz, Anna; Karpacz, Jarosław; Pavlov, Daniel; Rudawska, Joanna (Orientacja przedsiębiorcza i wyniki w kontekście dynamizmu rynku: podobieństwa i odmiennościmiędzy polskimi i bułgarskimi przedsiębiorstwami, 2018)
The aim of the study is to identify the similarities and differences regarding the level of entrepreneurial orientation and the performance results between Polish and Bulgarian companies in the context of the market dynamism they operate on. The subject is part of the research stream on discovering the context role in studying the effects of EO. In this research, an international (two-country) sample was used, which sheds light on the occurrence of EO in Polish companies in comparison to Bulgarian companies, with a simultaneous diagnosis of the level of results in these companies and the market dynamism that the companies perform their business with. Quantitative empirical studies were conducted using the CAWI method The research sample included micro, small, medium and large companies operating in Poland and in Bulgaria. Similarities and differences were recognized on the level of entrepreneurial orientation, company results and market dynamism in various perspectives, i.e. the size, the profile of business activities of the company according to PKD and the age of the company.
Management Forum, 2018, vol. 6, no. 4, s. 40-47
Keywords: entrepreneurial orientation; performance; market dynamism; orientacja przedsiębiorcza; wyniki; dynamizm rynku